Synthesis and fluorescent properties of N(9)-alkylated 2-amino-6-triazolylpurines and 7-deazapurines - Andrejs Šišuļins; Jonas Bucevičius; Yu-Ting Tseng; Irina Novosjolova; Kaspars Traskovskis; Ērika Bizdēna; Huan-Tsung Chang; Sigitas Tumkevičius; Māris Turks (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of novel fluorescent N(9)-alkylated 2-amino-6-triazolylpurine and 7-deazapurine derivatives is described. A new C(2)-regioselectivity in the nucleophilic aromatic substitution reactions of 9-alkylated-2,6-diazidopurines and 7-deazapurines with secondary amines has been disclosed. The obtained intermediates, 9-alkylated-2-amino-6-azido-(7-deaza)purines, were transformed into the title compounds by CuAAC reaction. The designed compounds belong to the push–pull systems and possess promising fluorescence properties with quantum yields in the range from 28% to 60% in acetonitrile solution. Due to electron-withdrawing properties of purine and 7-deazapurine heterocycles, which were additionally extended by triazole moieties, the compounds with electron-donating groups showed intramolecular charge transfer character (ICT/TICT) of the excited states which was proved by solvatochromic dynamics and supported by DFT calculations. In the 7-deazapurine series this led to increased fluorescence quantum yield (74%) in THF solution. The compounds exhibit low cytotoxicity and as such are useful for the cell labelling studies in the future.